Treatment of the journalistic coverage of natural phenomena in La Hora and El Heraldo newspapers: Eruptive process of the Tungurahua volcano in 2006 and 2012 - Sánchez Peña, Marco Iván (Scripta Mundi, 2025)
The journalistic coverage of the eruptive process of the Tungurahua Volcano began in 1999 with the reactivation of the colossus, and reached its peak in 2006 when the greatest emergency occurred with explosions that resulted in the emission of lahars and ash around the city of Baños de Agua Santa. This paper studies the journalistic coverage of the natural disaster by the newspapers La Hora and El Heraldo of the city of Ambato, two local newspapers with provincial and regional circulation. With a descriptive quantitative approach, a 7-year study corpus was constructed. Artificial weeks (week sampling) were established in order to collect the publications to be analyzed with the orientation of the content analysis technique. The results indicate that the event coverage has a conjunctural logic not attached to a consecutive planning but close to the evolution of the emergency. It was identified that the prevailing genre was news followed by reports and briefs, indicating that the media generated information as the emergency unfolded